1988
DOI: 10.1128/jb.170.1.422-430.1988
|View full text |Cite
|
Sign up to set email alerts
|

Rate and topography of cell wall synthesis during the division cycle of Salmonella typhimurium

Abstract: The rates of synthesis of peptidoglycan and protein during the division cycle of Salmonella typhimurium have been measured by using the membrane elution technique and differentially labeled diaminopimelic acid and leucine. The cells were labeled during unperturbed exponential growth and then bound to a nitrocellulose membrane by filtration. Newborn cells were eluted from the membrane with fresh medium. The radioactivity in the newborn cells in successive fractions was determined. As the cells are eluted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 71 publications
9
51
1
Order By: Relevance
“…We observed an increase in the ratio of DAP to leucine in the older cells, peaking at 0-7 during the cell cycle. This is in agreement with results obtained using the backwards membrane-elution method (Cooper, 1988 ; ; unpublished results). The bars in Fig.…”
Section: Composition Of Peptidoglycan Synthesized At Diferent Times Dsupporting
confidence: 82%
See 4 more Smart Citations
“…We observed an increase in the ratio of DAP to leucine in the older cells, peaking at 0-7 during the cell cycle. This is in agreement with results obtained using the backwards membrane-elution method (Cooper, 1988 ; ; unpublished results). The bars in Fig.…”
Section: Composition Of Peptidoglycan Synthesized At Diferent Times Dsupporting
confidence: 82%
“…Results obtained using the membrane-elution method have led to our understanding of the pattern of DNA replication during the bacterial division cycle (Cooper,199 1 a). Membrane-elution studies with S. typhimurium 2616 and E. coli NC3 have also shown that there is a reproducible non-exponential pattern of peptidoglycan synthesis during the division cycle (Cooper, 1988 ;. Theoretical considerations prompted by these findings suggest that the point at which septal peptidoglycan synthesis is greatest may not be at the end of the division cycle.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations